Sistem Informasi Penjualan Furniture Berbasis Web dengan Metode Rapid Application Development Development (RAD) pada Gemakasih Furniture - Malau , Emerson P; Silalahi , Riwanto S (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2023)
Furniture is an asset that is traded in general to the wider community, this sale includes sales such as chairs, cabinets which are made of wood. Sales activities are generally carried out man to man or still using a manual system, where the customer must first come to the sales outlet to place an order. This can be said to be less effective because from an economic point of view it consumes a lot of resources. With the existence of a furniture information system that contains sales of goods, consumers do not need to come to the place to place an order, now customers or customers can access a website-based information system through devices connected to the internet. In addition, product providers will be further assisted by a digital product marketing system that can be seen by many consumers. To support this, a publication information system is needed that can accommodate all existing sales activities. In this design, a method is used, namely the Rapid Application Development (RAD) method